Hegemoni Partai Keadilan Sejahtera Pada Pilkada Kota Depok 2020 - Muhammad Ariel Azfar Hadi; Danis Tri Saputra Wahidin (JPP (Jurnal Politik Profetik), 2024)
The Prosperous Justice Party (PKS) is an Islamic-based political party that has won the Depok City Regional Election (Pilkada) four times in a row since the first Pilkada was held in the city. The consistent change in leadership in Depok raises questions about PKS’s hegemonic practices to maintain and expand its influence among the people of Depok. This research aims to identify PKS Depok’s hegemonic practices according to Antonio Gramsci’s theory, which emphasizes creating ideological consensus, the role of intellectuals, and political leadership. The study uses qualitative methods, collecting data through interviews and literature review. It is conducted in Depok, focusing on the DPD PKS Depok and the 2020 Depok City regional Election as a case study. The study concludes that Idris-Imam, PKS-backed candidates for Mayor and Vice Mayor of Depok, won the election through the dissemination of the Rahmatan Lil Alamin Islamic ideology, the role of intellectuals such as ustad, and educational institutions, as well as the religious political leadership of Kiai Idris, the former Depok Mayor.